2008
DOI: 10.1093/annonc/mdn176
|View full text |Cite
|
Sign up to set email alerts
|

Significant improvement in survival of patients presenting with metastatic colon cancer in the south of The Netherlands from 1990 to 2004

Abstract: Palliative chemotherapy significantly improved OS in unselected patients with metastatic colon cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(28 citation statements)
references
References 20 publications
2
26
0
Order By: Relevance
“…Our finding of more patients receiving active treatment is consistent with other reports of an increasing use of new agents 10,11 in routine practice. Similarly, separate studies have reported survival changes over time, 12,13 which are of similar magnitude to what we observed. In the absence of comprehensive treatment data in these previous studies, the survival gains were mostly attributed to increased chemotherapy use, with stage migration and earlier diagnosis also thought to be important factors.…”
Section: Discussionsupporting
confidence: 91%
“…Our finding of more patients receiving active treatment is consistent with other reports of an increasing use of new agents 10,11 in routine practice. Similarly, separate studies have reported survival changes over time, 12,13 which are of similar magnitude to what we observed. In the absence of comprehensive treatment data in these previous studies, the survival gains were mostly attributed to increased chemotherapy use, with stage migration and earlier diagnosis also thought to be important factors.…”
Section: Discussionsupporting
confidence: 91%
“…Advances in surgical and oncological treatment over the past decades have improved prognosis for stage IV colorectal cancer patients [4,19]. In addition, a better understanding of the underlying tumor biology and the identification of prognostic factors highlighted that stage IV colorectal cancer patients are an inhomogeneous group and treatment must be individualized [6,20].…”
Section: Discussionmentioning
confidence: 99%
“…Before the use of chemotherapy, initial survival of stage IV colorectal cancer patients with supportive care was six months [4,19]. With the successive introduction of chemotherapeutic agents over the past two decades, median survival has been increased to 14-16 months.…”
Section: Discussionmentioning
confidence: 99%
“…14,21 While survival of patients with metastases confined to the liver was equal to that of peritoneal carcinomatosis in 1995-2001, populationbased survival of these patients rose considerably from 8 to 12 months in the most recent period, thanks to the introduction of more efficient chemotherapeutics. 30 Patients with peritoneal carcinomatosis do not seem to benefit at population level from the availability of the new treatment arsenal.…”
Section: Epidemiologymentioning
confidence: 99%